Pengaruh Dimensi Fraud Diamond dan Religuisitas Terhadap Perilaku Kecurangan Akademik: (Studi Empiris pada Mahasiswa/I Prodi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Nusa Nipa Maumere) - Fransiska Trisnawati; Konstantinus Pati Sanga; Fransiscus De Romario (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to analyze the influence of diamond fraud dimensions and religiosity on the academic fraudulent behavior of accounting students at the Faculty of Economics and Business, Nusa Nipa University, Maumere. This type of research is quantitative research with an associative approach. The sampling technique uses probability sampling, a type of stratified random sampling method, where the sample is determined and determined randomly by dividing the population into several sub-classes and semesters with a sample size of 84 people. The data collection technique used (google form) which was distributed to 84 respondents. Data analysis used multiple linear regression using the Statistical Package for the Social Sciences (SPSS) version 25. The results of this study showed that partially pressure did not have a significant and positive effect on academic cheating behavior. Opportunity does not have a significant and positive effect on academic cheating behavior. Rationalization has a significant and positive effect on academic cheating behavior. Ability does not have a significant and positive effect on academic cheating behavior. Religiousness does not have a significant and negative effect on academic cheating behavior. Simultaneously, the results of this research show that the variables pressure, opportunity, rationalization, ability and religiosity have a significant and positive effect on academic cheating behavior.